Hadith #4499 - Sunan Abi Dawud - Alqama bin Wa'il bin Hjr علقمة بن وائل بن حجر; Muhammad bin Awf bin Sufyan محمد بن عوف بن سفيان الطائي; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Yazid bin Ata'a bin Yazid يزيد بن عطاء بن يزيد (Sunan Abi Dawud)
I was with the Prophet (ﷺ) when a man who was a murderer and had a strap round his neck was brought to him. He then called the legal guardian of the victim and asked him: Do you forgive him? He said: No. He asked: Will you accept the blood-money? He said: No. He asked: Will you kill him? He said: Yes. He said: Take him. When he turned his back, he said: Do you forgive him? He said: No. He said: Will you accept the blood-money? He said: No. He said: Will you kill him? He said: Yes. He said: Tak
Grade: Sahih